The effect of probiotics on functional constipation in adults: Double-blind, randomized, placebo-controlled study - Mitelmão, Fabiana Cristina Rosa (Medicine (Baltimore), 2021)
BACKGROUND: : Evacuation disorders are common in industrialized countries, affecting an average of 15% to 20% of the healthy adult population. Probiotic therapy can reduce functional constipation and increase both the number of weekly bowel movements and quality of stools. Based on the hypothesis that a combination of more strains may provide better results for constipation and facilitate adherence to treatment, this study will evaluate the efficacy and safety of a combination of different strains of Lactobacillus sp. and Bifidobacterium sp. in functional constipation. METHODS: : A single-centre trial of adults aged 20 to 80 years with intestinal constipation will be conducted at a Gastroenterology Clinic in Sorocaba, State of São Paulo, Brazil. Participants will be allocated into 3 groups receiving: 1. mixture of 3 probiotics: [Lactobacillus acidophilus, Bifidobacterium bifidum, and Lactobacillus rhamnosus (3 × 10(9) CFU)]; 2. mixture of 8 probiotics [Lactobacillus acidophilus, Bifidobacterium bifidum, Lactobacillus rhamnosus, Lactobacillus paracasei, Bifidobacterium longum, Bifidobacterium lactis, Lactobacillus defensis, Bifidobacterium animallis (8 × 10(9) CFU)]; or 3. placebo, for 4 weeks. The outcomes of interest will be change in frequency of weekly bowel movements, change in stool quality according to the 4–6 Bristol scale, number of volunteer withdrawal, number of adverse events and number of serious adverse effect. DISCUSSION: The probiotic products are expected to induce beneficial changes in the intestinal microbiota, thereby increasing intestinal frequency to over 3 times a week and improving stool quality. The results can guide patients and healthcare practitioners and help in decision-making in the treatment of functional constipation. TRIAL REGISTRATION AND REGISTRY NAME: ClinicalTrials.gov Identifier: NCT04437147: The Effect of Probiotics on Functional Constipation in Adults: Study protocol for Double blind, Randomized, Placebo controlled Study PROTOCOL VERSION: Version 01 August 30, 2020.